Stylistic Analysis of Roald Dahl’s Cinderella - Henni, Henni (k@ta: A Biannual Publication on the Study of Language and Literature, 2010)
The paper presents a stylistic analysis of a rhyme, Cinderella, taken from Dahl’s rhyme collection, Revolting Rhymes. Roald Dahl is famous for his ability in creating extraordinary stories, in which linguistic elements, such as sounds and words, are manipulated to create an amusing story that has an unpredictable plot. The discussion covers an analysis of the narrative structure and the linguistic style applied in the rhyme, together with the discussion of the author’s purpose of applying such style. From the analysis it is found out that the style Dahl applies in the rhyme is especially useful for foregrounding.